2012
DOI: 10.2478/s13382-012-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exposure route on the distribution and excretion of hexachloronaphthalene in rats

Abstract: Objectives: Polychlorinated naphthalenes (PCNs), like other persistent organic pollutants (POPs), are widespread, global environmental contaminants. These compounds still represent a great environmental problem, mostly because of the risk of secondary air pollution. They are characterized by long durability and tendency to bioaccumulate, which means that they are practically ubiquitous in all environmental media and ecosystems. The aim of this study was to investigate the distribution and excretion of hexachlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
(43 reference statements)
2
6
0
Order By: Relevance
“…Our findings indicate that the L/A ratio decreased with time after administration, which is comparable with the results observed by Chen et al [44]. The gradually increasing concentration of HxCN in the adipose tissue after administration was also observed in a previous study on the distribution of this compound in male rats [24]. Our present findings also indicate that HxCN penetrates into the fetus, reaching a level of 0.05% dose/g tissue, which is comparable to the findings obtained by Chen et al [44] following the exposure of the subjects to TCDD (0.053% dose/g tissue).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings indicate that the L/A ratio decreased with time after administration, which is comparable with the results observed by Chen et al [44]. The gradually increasing concentration of HxCN in the adipose tissue after administration was also observed in a previous study on the distribution of this compound in male rats [24]. Our present findings also indicate that HxCN penetrates into the fetus, reaching a level of 0.05% dose/g tissue, which is comparable to the findings obtained by Chen et al [44] following the exposure of the subjects to TCDD (0.053% dose/g tissue).…”
Section: Discussionsupporting
confidence: 92%
“…In the case of mothers, the greatest retention was observed in the livers, while the opposite was observed in the fetuses; similarly, earlier studies on the distribution of hexachloronaphthalene in male rats also found the highest concentration to be in the liver [24]. This is probably due to the differences present in the fetal liver circulation.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…This global concern is attributable to the toxicity, bioaccumulation, and long-range transport of PCNs, which are similar to those of dioxins and dioxin-like chemicals . Studies in laboratory animals on the toxicity of PCNs reported dermal lesions, oxidative stress, lipid peroxidation, genotoxicity, carcinogenicity, neurotoxicity, and reproductive and developmental toxicity. Known effects of PCNs in humans include chloracne, liver dysfunction, systemic symptoms of digestive problems, anorexia, nausea, vertigo, and even death. Environmental pollution by PCNs is both historical and ongoing.…”
Section: Introductionmentioning
confidence: 99%